Massive Transfusion Protocols in Obstetric Hemorrhage: Theory versus Reality - Salmanian, Bahram; Clark, Steven L.; Hui, Shiu-Ki R.; Detlefs, Sarah; Aalipour, Soroush; Meshinchi Asl, Nazlisadat; Shamshirsaz, Alireza A. (American Journal of Perinatology, 2021)
Objective Massive transfusion protocols are widely implemented in obstetrical practice in case of severe hemorrhage; however, different recommendations exist regarding the appropriate ratios of blood product components to be transfused. We report our extensive experience with massive component transfusion in a referral center in which the standard massive transfusion protocol is modified by ongoing clinical and laboratory evaluation.Study Design A retrospective chart review of all patients who had massive transfusion protocol activation in a level 4 referral center for obstetrical practice was performed from January 2014 to January 2020. Data collected included the etiology of obstetrical hemorrhage, number of blood products of each type transfused, crystalloid infusion, and several indices of maternal morbidity and mortality. Data are presented with descriptive statistics.Results A total of 62 patients had massive transfusion protocol activation, of which 97% received blood products. Uterine atony was found to be the most common etiology for massive hemorrhage (34%), followed by placenta accreta spectrum (32%). The mean estimated blood loss was 1,945 mL. A mean of 6.5 units of packed red blood cells, 14.8 units of fresh frozen plasma and cryoprecipitate, and 8.3 units of platelets were transfused per patient. No maternal deaths were seen.Conclusion The ratios of transfused packed red blood cell to fresh frozen plasma/cryoprecipitate and of packed red blood cell to platelet units varied significantly from the fixed initial infusion ratio called for by our massive transfusion protocol resulting in universally favorable maternal outcomes. When rapid laboratory evaluation of hematologic and clotting parameters is available, careful use of this information may facilitate safe modification of an initial fixed transfusion ratio based on etiology of the hemorrhage and individual patient response.Key Points
Keywords: obstetric hemorrhage; postpartum hemorrhage; massive transfusion